Further morphological evidence on South African earliest Homo lower postcanine dentition: Enamel thickness and enamel dentine junction. Issue 96 (July 2016) - Pan, Lei; Dumoncel, Jean; de Beer, Frikkie; Hoffman, Jakobus; Thackeray, John Francis; Duployer, Benjamin; Tenailleau, Christophe; Braga, José
Abstract: The appearance of the earliest members of the genus Homo in South Africa represents a key event in human evolution. Although enamel thickness and enamel dentine junction (EDJ) morphology preserve important information about hominin systematics and dietary adaptation, these features have not been sufficiently studied with regard to early Homo . We used micro-CT to compare enamel thickness and EDJ morphology among the mandibular postcanine dentitions of South African early hominins ( N = 30) and extant Homo sapiens ( N = 26), with special reference to early members of the genus Homo . We found that South African early Homo shows a similar enamel thickness distribution pattern to modern humans, although three-dimensional average and relative enamel thicknesses do not distinguish australopiths, early Homo, and modern humans particularly well. Based on enamel thickness distributions, our study suggests that a dietary shift occurred between australopiths and the origin of the Homo lineage. We also observed that South African early Homo postcanine EDJ combined primitive traits seen in australopith molars with derived features observed in modern human premolars. Our results confirm that some dental morphological patterns in later Homo actually occurred early in the Homo lineage, and highlight the taxonomic value of premolar EDJ morphology in hominin species.